2018
DOI: 10.1002/pola.29076
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and crosslinking reaction of polyacetylenes substituted with benzoxazine rings: Thermally highly stable benzoxazine resins

Abstract: Novel polyacetylenes, poly(1) and poly(2) substituted with benzoxazine rings were synthesized by the polymerization of the corresponding acetylene monomers 1 and 2 using Rh catalysts, [(nbd)RhCl]2, and (nbd)Rh+B–Ph4 (nbd = 2,5‐norbornadiene). The polymers were heated at 250 °C under N2 to obtain the corresponding polybenzoxazine resins, poly(1)′ and poly(2)′ possessing polyacetylene main chains via the ring‐opening polymerization of the benzoxazine moieties. The polyacetylene backbones were maintained after cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…It can be attributed to the fact that with the ring-opening of oxazine rings, the formation of H-bonds between intramolecular and intermolecular chains increased. This trends were well consistent with the published literatures [41,42].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…It can be attributed to the fact that with the ring-opening of oxazine rings, the formation of H-bonds between intramolecular and intermolecular chains increased. This trends were well consistent with the published literatures [41,42].…”
Section: Resultssupporting
confidence: 94%
“…The characteristic absorption observed at around 3289–3555 cm −1 can be mainly assigned to the intermolecular and intramolecular H-bonds, which were formed between the hydroxyl and nitrogen atoms generated from the ring-opening polymerization of oxazine rings [39,40]. As the references reported that the intramolecular H-bonds could turn into intermolecular H-bonds when the temperature went on which contributed to the increase of surfce free energy of cured matrix [41,42]. It was well known that the formation of hydrogen bonds was sensitive to temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly( 1 )′ exhibited no clear absorption peaks assignable to the original benzoxazine rings. These IR spectroscopic data of the monomer and the polymers before and after heating confirmed the occurrence of ring‐opening reaction of the benzoxazine moieties upon heating to afford a network polymer …”
Section: Resultssupporting
confidence: 54%
“…We have reported various π‐conjugated polymers including substituted polyacetylenes and polyphenyleneethynylenes, some of which adopt regulated higher‐order structures originating from the rigid main chain . We have recently synthesized polyacetylenes substituted with benzoxazine rings to find the high thermal stability presumably due to the synergistic effect of the π‐conjugated backbone and benzoxazine moieties . The combination of π‐conjugation and benzoxazine is a promising candidate of future coming high‐performance thermosetting resins exhibiting excellent heat resistance and thermal conductivity compared with conventional benzoxazine resins.…”
Section: Introductionmentioning
confidence: 99%